2007
DOI: 10.1128/jvi.01917-06
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Hsp90 in Assembly and Nuclear Import of Influenza Virus RNA Polymerase Subunits

Abstract: Transcription and replication of the influenza virus RNA genome occur in the nuclei of infected cells through the viral RNA-dependent RNA polymerase consisting of PB1, PB2, and PA. We previously identified a host factor designated RAF-1 (RNA polymerase activating factor 1) that stimulates viral RNA synthesis. RAF-1 is found to be identical to Hsp90. Here, we examined the intracellular localization of Hsp90 and viral RNA polymerase subunits and their molecular interaction. Hsp90 was found to interact with PB2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
215
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(230 citation statements)
references
References 43 publications
12
215
2
1
Order By: Relevance
“…Thus, it has been suggested that PB1 and PA form a heterodimeric complex that is transported to the nucleus by association to RanBP5, 77,78 but other studies suggested a role for Hsp90 in the transport of PB1-PB2 and PB1-PA heterodimers. 79 Recently, studies of crosscorrelation fluorescence spectroscopy have supported the formation of PB1-PA heterodimers in the cytoplasm and their transport to the nucleus independently of the PB2 subunit. 80 In addition, mutation analyses of the PB2 NLS indicated that the transport of PB2 to the nucleus and the formation of a functional polymerase complex are closely correlated events 14 and represent host-regulated steps in the virus multiplication cycle.…”
Section: To Switch or Not To Switchmentioning
confidence: 99%
“…Thus, it has been suggested that PB1 and PA form a heterodimeric complex that is transported to the nucleus by association to RanBP5, 77,78 but other studies suggested a role for Hsp90 in the transport of PB1-PB2 and PB1-PA heterodimers. 79 Recently, studies of crosscorrelation fluorescence spectroscopy have supported the formation of PB1-PA heterodimers in the cytoplasm and their transport to the nucleus independently of the PB2 subunit. 80 In addition, mutation analyses of the PB2 NLS indicated that the transport of PB2 to the nucleus and the formation of a functional polymerase complex are closely correlated events 14 and represent host-regulated steps in the virus multiplication cycle.…”
Section: To Switch or Not To Switchmentioning
confidence: 99%
“…On the contrary, replication of viral RNPs does not require capped primers and occurs by the synthesis of a complementary RNA (cRNA) intermediate, which is a complete copy of the virion RNA (vRNA) (Hay et al, 1982), and serves as template for the generation of progeny vRNAs. Both vRNAs and cRNAs are encapsidated into RNP structures during replication (reviewed by Elton et al, 2005).In addition to the RNP-associated polymerase, soluble polymerase complexes have been detected in infected cells (Detjen et al, 1987) and the interaction of cellular proteins with the polymerase complex has been described (Deng et al, 2006;Mayer et al, 2007;Momose et al, 2002;Naito et al, 2007) (N. Jorba and others, unpublished data). To characterize these soluble intracellular polymerase complexes we have addressed their expression and purification from human cells.…”
mentioning
confidence: 99%
“…In addition to the RNP-associated polymerase, soluble polymerase complexes have been detected in infected cells (Detjen et al, 1987) and the interaction of cellular proteins with the polymerase complex has been described (Deng et al, 2006;Mayer et al, 2007;Momose et al, 2002;Naito et al, 2007) (N. Jorba and others, unpublished data). To characterize these soluble intracellular polymerase complexes we have addressed their expression and purification from human cells.…”
mentioning
confidence: 99%
“…Hsp90 has been believed to facilitate viral protein folding and activity of non-structural proteins such as polymerase, protease and helicase as well as the structural proteins [3]. The polymerase of several viruses require Hsp90 for genome replication which include influenza virus A [12], herpes simplex virus [26], flock house virus [27] and vesicular stomatitis virus and treatment with Hsp90 inhibitors such as geldanamycin and 17-AAG lead to degradation of polymerase complexes [28,22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that Hsp90 also binds to the viral components mainly to the RNA polymerase affecting the assembly and nuclear transport of polymerase [12]. Researchers have found a tetranortriterpenoid compound called gedunin, obtained from the Indian neem tree (Azadirachta indica), to be active against the 90 kDa Hsp90 by binding directly to its helper protein p23 leading to its inactivation [13,14].…”
Section: Introductionmentioning
confidence: 99%